The Effectiveness of Using Montessori-Based Wordwall Educational Games on Elementary School Students' Beginning Reading Skills at Sanggar Bimbingan Pandan Kuala Lumpur Malaysia - Azaria, Elvina; Perwita, Suci (Universitas Pahlawan Tuanku Tambusai, 2025)
Reading is a fundamental skill essential for academic success; however, in reality, there are still students who struggle with reading because they cannot comprehend the commands or content within books. This skill is particularly vital, as much of human knowledge is acquired through reading. Speaking and reading are uniquely important in the development of communication and knowledge. This research aims to determine whether the use of Montessori-based word wall educational games can influence early reading skills of first-grade students at Sanggar Pandan Guidance, Kuala Lumpur, Malaysia. This study employs a quantitative approach using an experimental method. The research was conducted at Studio Bimbingan Aisyiyah, located on Jl. Kijing No. 15, Kampung Pandan, Kuala Lumpur. The population consists of first-grade elementary students at Sanggar Pandan Guidance, with a sample size of 8 students. The instruments used were performance tests and observations, while the data analysis techniques included expert judgment validity testing and one-sample t-test hypothesis testing. The results show that during the pre-test (before using the educational games), students' early reading skills were categorized as “fair” with a percentage of 58% and a t-value of 177.193 1.89458. After implementing the word wall educational games, the post-test results indicated a significant improvement, with students achieving a “good” category at 84.37% and a t-value of 105.417 1.89458. Based on these findings, it can be concluded that the use of Montessori-based word wall educational games is effective in improving the early reading skills of first-grade elementary students at Sanggar Pandan Guidance, Kuala Lumpur, Malaysia.